Pengembangan Media Pembelajaran “Papin” (Papan Pintar) Tentang Keragaman Suku Bangsa dan Budaya Kelas IV di SD Negeri 101767 Tembung - Maryana Meldrin Rosres; Lidia Simanihuruk; Elvi Mailani; Masta Marselina Sembiring; Husna Parluhutan Tambunan (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
The problem in this research is formulated into three main questions: (1) How to develop "PAPIN" (Smart Board) learning media on ethnic and cultural diversity for Grade IV students at SD Negeri 101767 Tembung? (2) How to validate the "PAPIN" learning media to ensure its appropriateness and quality for use in the classroom? (3) How effective is the use of the "PAPIN" (Smart Board) learning media in improving students' understanding of ethnic and cultural diversity in a primary school setting? The main objectives of this research are: (1) To develop feasible and relevant "PAPIN" learning media that supports the learning of ethnic and cultural diversity in accordance with the needs of Grade IV students at SD Negeri 101767 Tembung. (2) To produce a practical and user-friendly digital learning tool that can be integrated into classroom activities. (3) To evaluate the effectiveness of the media in improving learning outcomes, particularly students' knowledge, engagement, and appreciation of cultural diversity. This research adopts the 4D (Define, Design, Develop, and Disseminate) development model, a systematic method for creating and validating educational products. The research subjects are fourth-grade students from SD Negeri 101767 Tembung, selected as they represent the target users of the media. Data were collected through classroom observations, documentation, expert validation sheets, student response questionnaires, and evaluation instruments to measure the learning outcomes. The findings of this research are expected to contribute to the development of innovative, technology-based instructional tools in elementary education, particularly in promoting multicultural awareness and inclusive learning environments.